On the smoothness of bounded invariant manifolds of linear inhomogeneous extensions of dynamical systems - Hrod, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish sufficient conditions for the existence of smooth bounded invariant manifolds of dynamical systems.